ChemInform Abstract: Physical Chemistry of Ionic Liquids: Inorganic and Organic as Well as Protic and Aprotic. Issue 3 (22nd January 2013) - Angell, C. A.; Xu, W.; Yoshizawa‐Fujita, M.; Hayashi, A.; Belieres, J.‐P.; Lucas, P.; Videa, M.; Zhao, Z.‐F.; Ueno, K.; Ansari, Y.; et al., et al.
Abstract Review: 83 refs.